Orchids From Five Districts in Fakfak Regency, West Papua: Diversity and Distribution - Reza Saputra (Jurnal Penelitian Hutan dan Konservasi Alam, 2021)
A study of the diversity and distribution of orchids has been conducted in five districts in Fakfak Regency, i.e. Kokas, Fakfak Tengah, Fakfak, Wartutin, and Karas. This study was conducted based on current condition that research on orchid inventory has never been carried out in Fakfak Regency. Therefore, there is lack information and report related to the data of orchids collection from this regency. The objective of the research was to provide a preliminary note on the diversity and distribution of orchids in the Fakfak Regency. The study was carried out using the Visual Encounter Survey and the Purposive Exploration method. The result determined 67 collection numbers consisting of 49 epiphytic orchids, 16 terrestrial orchids, and two holomycotrophic orchids classified into 33 genera and 67 species. Fakfak Tengah District has the most diverse orchids species compared to other districts, viz. 37 species.